FEATURES OF THE DEVELOPMENT OF CONTEMPORARY FINE ARTS IN UZBEKISTAN (International journal of artificial intelligence, 2026)
The modern visual arts of Uzbekistan have gone through significant changes and transformations over the past decades, reflecting a wide range of socio-cultural, political and economic changes in the country. The peculiarities of the development of modern Uzbek fine art can be considered from various points of view, taking into account both traditional cultural values, as well as international influences and the latest trends in contemporary art.